Effectiveness of the game-based learning over traditional teaching-learning strategy to instruct pharmacology for Phase II medical students - Anupama M Gudadappanavar; Jyoti M Benni; Shivalingappa B Javali (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Game-based education is fast becoming an innovative teaching approach in the field of medical education. Traditional review sessions (tutorials) are mainly focused on instructor-based learning and they help to review concepts previously taught in the lecture class. The primary objective was to evaluate the cognitive learning of students in game based learning (GBL) as compared to the conventional review sessions. The secondary objectives were to assess the perception and feedback of students regarding GBL and conventional review sessions. MATERIALS AND METHODS: An interventional GBL study was designed for 2nd year MBBS students. The enrolled students were randomly assigned to either tutorial (Group A) or GBL (Group B), and informed consent was obtained. Group B students were further divided into smaller groups, and for Group A, the traditional tutorial method was followed. For both the groups, a multiple choice question (MCQ) pre-test and post-test was conducted on the selected topics. A total of 15 MCQs with gradually increasing difficulty were used in the GBL. For each group of students, one student would be on hot seat by answering the questions and then continued the game. Lifelines were provided. RESULTS: From the pretest and posttest scores, students performed better in Group B (39.53%) than Group A (18.43%) with respect to the knowledge score, and the difference was statistically significant. Students' perception and feedback regarding GBL were very enthusiastic and promising than the tutorial group. Largely, students commented that GBL was unique, active participation, fun, and novel learning style. CONCLUSIONS: GBL is a student-centered learning and showed more effective than the traditional tutorials in understanding the topic and was more enjoyable by students.